Interferon-α receptor antisense oligonucleotides reduce neuroinflammation and neuropathology in a mouse model of cerebral interferonopathy - Barney Viengkhou; Christine Hong; Curt Mazur; Sagar Damle; Nicholas B. Gallo; Terry C. Fang; Kate Henry; Iain L. Campbell; Fredrik Kamme; Markus J. Hofer (The Journal of Clinical Investigation, 2024)
Chronic and elevated levels of the antiviral cytokine IFN-α in the brain are neurotoxic. This is best observed in patients with genetic cerebral interferonopathies such as Aicardi-Goutières syndrome. Cerebral interferonopathies typically manifest in early childhood and lead to debilitating disease and premature death. There is no cure for these diseases with existing treatments largely aimed at managing symptoms. Thus, an effective therapeutic strategy is urgently needed. Here, we investigated the effect of antisense oligonucleotides targeting the murine IFN-α receptor (Ifnar1 ASOs) in a transgenic mouse model of cerebral interferonopathy. Intracerebroventricular injection of Ifnar1 ASOs into transgenic mice with brain-targeted chronic IFN-α production resulted in a blunted cerebral interferon signature, reduced neuroinflammation, restoration of blood-brain barrier integrity, absence of tissue destruction, and lessened neuronal damage. Remarkably, Ifnar1 ASO treatment was also effective when given after the onset of neuropathological changes, as it reversed such disease-related features. We conclude that ASOs targeting the IFN-α receptor halt and reverse progression of IFN-α–mediated neuroinflammation and neurotoxicity, opening what we believe to be a new and promising approach for the treatment of patients with cerebral interferonopathies.